اردومشابہ الصوت حروف اور اردو اعراب کا جواز: The Justification of Urdu Letters with Similar Sounds and Diacritics - ڈاکٹر عبدالستار ملک (Tashkeel e Jadeed, 2024)
Although Urdu script is derived from the Arabic script. But Urdu differs from Arabic in its nature and unlike Arabic, some sounds are pronounced like each other. Due to that some experts object to Urdu script and suggest the removal of letters with similar sounds. But the removal of these letters can create many complexities and difficulties which cannot be resolved. These eight specific sounds of Urdu are common to Pakistani languages ​​such as Punjabi, Sindhi, Pashto, Balochi, Kashmiri, and other local languages. How is it possible to exclude these words from all these languages? These sounds are the valuable capital of world languages ​​like Persian and Arabic. With this collaboration, Urdu emerges as a great global and scientific language. By removing these letters, Urdu will suffer a great loss in terms of knowledge. There will be an encounter, which cannot be compensated. In short, this change is not feasible in context with Urdu historical background and present linguistic geographical condition.. The Urdu script is non- diacritical in its nature and diacritics in Urdu are not arranged in the same way as in Arabic. However, it is necessary to organize the essential diacritics in the basic textbooks. This article argues and analyses the situation.